Reassessing the value of gastroscopy for the investigation of dyspepsia. Issue 1 (5th August 2017) - Ching, Hey-Long; Hale, Melissa F; Sidhu, Reena; McAlindon, Mark E
Abstract : Objective: To evaluate the diagnostic yield of investigating dyspepsia with oesophagogastroduodenoscopy (OGD) with or without mucosal biopsy. Design: Retrospective service evaluation study. Setting: Two teaching hospitals: The Royal Hallamshire Hospital and Northern General Hospital, Sheffield Teaching Hospitals NHS Foundation Trust, UK. Patients: 500 patients, 55 years of age and over, who underwent OGD to investigate dyspepsia were included. The study period included a 3-month window. All OGDs were performed on an outpatient basis. Interventions: Data were extracted from electronic OGD records within the study period. Main outcome measures: Diagnostic yield provided by endoscopic examination and histological assessment. Results: 378 patients (75.6%) were reported to have some form of endoscopic abnormality, and 417 patients (83.4%) had biopsies taken. The most common findings at OGD were gastritis (47.2%) and oesophagitis (24.4%). Oesophagogastric malignancy was seen in 1%. Diagnoses made endoscopically or histologically that would not have been appropriately managed by empirical therapies were seen in 16.2%. Conclusion: OGD in dyspepsia influences patient management in approximately one-sixth of cases. However, the majority of patients are sufficiently managed with Helicobacter pylori testing and eradication and/or a trial of proton pump inhibitor therapy. Further non-invasive approaches are needed to identify patients who need endoscopy for biopsy or therapy.